2002
DOI: 10.1109/mei.2002.1014964
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of mixed insulating liquids for use in high-voltage transformers.1. Investigation of mixed liquids

Abstract: Moisture is recognized to be "enemy number one" for transformer insulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(69 citation statements)
references
References 9 publications
4
60
0
5
Order By: Relevance
“…However, the viscosity of natural esters is high, so an excessive content of natural esters will enhance the viscosity of the mixed oil. This conclusion is consistent with the results of Fofana et al [21], who also researched the electrical, physicochemical, and degradation properties of mixtures of mineral insulating oil with natural esters (olive oil) with different components. They found that hydrolysis of the natural esters increased the acid content of the mineral insulating oil and decreased the breakdown voltage of the mixed oil.…”
Section: Modification Of Non-nanoparticlessupporting
confidence: 92%
See 2 more Smart Citations
“…However, the viscosity of natural esters is high, so an excessive content of natural esters will enhance the viscosity of the mixed oil. This conclusion is consistent with the results of Fofana et al [21], who also researched the electrical, physicochemical, and degradation properties of mixtures of mineral insulating oil with natural esters (olive oil) with different components. They found that hydrolysis of the natural esters increased the acid content of the mineral insulating oil and decreased the breakdown voltage of the mixed oil.…”
Section: Modification Of Non-nanoparticlessupporting
confidence: 92%
“…There are basically three states of moisture in insulating liquids, which are the dissolved state, emulsified state, and dispersed state. The moisture content in insulating oil can largely influence the electrical properties, that is, increase the electrical conductivity and dissipation factor and lower the electric strength of transformer oil [21].…”
Section: Breakdown Voltage Of Mineral Insulating Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative moisture for oil is the dissolved moisture content of the oil relative to the maximum capacity of moisture that the oil can hold. The relative moisture W rel at a given temperature T is defined in terms of the actual moisture content in a liquid W abs versus the saturation limit W L (T) [25], as following:…”
Section: Moisture Content Of Oilsmentioning
confidence: 99%
“…The relative moisture for oil is the dissolved moisture content of the oil relative to the maximum capacity of moisture that the oil can hold. The relative moisture W rel at a given temperature T is defined in terms of the actual moisture content in a liquid W abs versus the saturation limit W L (T) [24], as following:…”
Section: Thermal Ageing Experiments Of Oil-paper Insulation Samplesmentioning
confidence: 99%